Islamic Ethical Literacy in the Use of Artificial Intelligence (AI) for Writing Scientific Articles among First Semester PAI Students at University - Willi Rahim Marpaung; Salminawati; Zaini Dahlan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced academic practices in higher education, including the process of writing scientific articles. While AI offers efficiency and accessibility in obtaining academic information, it also raises ethical concerns, particularly regarding academic integrity and responsible use of technology. This study aims to explore Islamic ethical literacy in the use of AI for writing scientific articles among first-semester students of the Islamic Religious Education (PAI) program at the Faculty of Tarbiyah and Teacher Training (FITK), Universitas Islam Negeri Sumatera Utara (UINSU). The research employs a qualitative phenomenological approach to understand students’ lived experiences, perceptions, and ethical considerations in utilizing AI during academic writing. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that students generally recognize AI as a supportive learning tool; however, their level of Islamic ethical literacy varies. Some students use AI as a means of academic assistance, such as generating ideas and clarifying concepts, while others tend to rely on AI excessively without adequate critical reflection. The study also identifies several Islamic ethical values guiding AI usage, including honesty (ṣidq), trustworthiness (amanah), responsibility (mas’uliyyah), and the pursuit of public benefit (maṣlaḥah). Factors influencing ethical literacy include religious education background, academic culture, lecturer guidance, and digital environment. The research concludes that strengthening Islamic ethical literacy is essential to ensure that AI supports intellectual development without compromising academic integrity or moral character. Integrating Islamic ethical principles into digital literacy education is therefore recommended for Islamic higher education institutions.